Complexes between Activated Protein C and Protein C Inhibitor Measured with a New Method - Strandberg, Karin; Astermark, Jan; Björgell, Ola; Becker, Charlotte; Nilsson, Paul E.; Stenflo, Johan (Thrombosis and Haemostasis, 2001)
A first clinical evaluation has been made of the performance of a newly devised immunofluorometric assay for measuring plasma concentrations of activated protein C (APC) in complex with protein C inhibitor (PCI). The method was compared with testing for other markers of hypercoagulability in a case-control study comprising 123 patients with clinical suspicion of deep vein thrombosis (DVT). The diagnosis was confirmed by ascending phlebography, and the thrombotic burden estimated with a newly developed scoring system. Receiver operating characteristics (ROC) curves calculated to demonstrate the discriminatory capacity of the methods, showed the area under the curves (AUCs) to be similar for the APC-PCI and D-dimer methods. However, in contrast to the D-dimer method, the APC-PCI method measures a well-defined analyte, a prerequisite for reliable comparisons of future clinical studies. The APC-PCI method appears to be particularly useful as a marker for detection of recently developed proximal thrombi.
Keywords: APC-PCI complex; immunofluorometric assay; deep vein thrombosis; case-control study; hypercoagulability markers